PREDICTION AND PREVENTION OF LIVER FAILURE AFTER MAJOR LIVER PRIMARY AND METASTATIC TUMORS RESECTION - A. D. Kaprin; D. V. Sidorov; N. A. Rubtsova; A. V. Leontyev; M. V. Lozhkin; L. O. Petrov; N. A. Grishin; T. N. Lazutina; I. V. Pylova; A. G. Isaeva (Исследования и практика в медицине, 2016)
Abstract Purpose of the study. Improvement of results of treatment in patients with primary and metastatic liver cancer by decreasing the risk of post-resection liver failure on the basis of the evaluation of the functional reserves of the liver.Materials and Methods. The study included two independent samples of patients operated about primary or metastatic lesions of the liver at the Department of abdominal Oncology, P. A. Hertsen MORI. The first group included 53 patients who carried out 13C-breath test metallimovie and dynamic scintigraphy of the liver in the preoperative stage in addition to the standard algorithm of examination. Patients of the 2nd group (n=35) had a standard clinical and laboratory examination, the patients were not performed the preoperative evaluation of the functional reserve of the liver, the incidences of total bilirubin, albumin and prothrombin time did not reveal a reduction of liver function. Post-resection liver failure have been established on the basis of the 50/50 criterion in the evaluation on day 5 after surgery.Results. Analysis of operating characteristics of the functional tests showed the absolute methacin breath test sensitivity (SE≥100%), high specificity (SP≥67%) of scintigraphy of the liver and the negative predictive value of outcome (VP≥100%) at complex use of two diagnostic methods. The incidence of PROPS in the study group was significantly 2 times higher in the control group –15,1% and 26.8%, respectively (p<0.001).Conclusion. The combination of preoperative dynamic scintigraphy of the liver with carrying out 13C-breath methacin test allows you to conduct a comprehensive evaluation of the liver functional reserve and can significantly improve preoperative evaluation and postoperative results of anatomic resection in patients with primary and metastatic liver lesions.